KONFLIK BATIN DALAM NOVEL RUMAH UNTUK ALIE KARYA LENN LIU: KAJIAN PSIKOLOGI SIGMUND FREUD - Najab Ridwansyah; Sumiman Udu; Marwati (Jurnal Bastra (Bahasa dan Sastra), 2025)
he purpose of this study is to describe the inner conflict in the novel Rumah Untuk Alie by Lenn Liu using the psychological study of Sigmund Freud. This type of research is library research, namely research supported by references in the form of novel texts or other book sources that cover the problems of this research. The data used in this study are written data in the form of novel texts related to the inner conflict in the novel Rumah Untuk Alie by Lenn Liu. The data source in this study is the novel Rumah Untuk Alie by Lenn Liu which is 262 pages long and published by Tekad Media Cakrawala, fourth edition April 2024. The technique used to collect data in this study is the intensive reading technique. The steps taken in analyzing the data are: data identification, data classification, and data interpretation. Based on the results of the study of inner conflict in the novel Rumah Untuk Alie by Leen Liu: in the Psychological Study of Sigmund Freud, it is concluded that the psychoanalytic theory put forward by Sigmund Freud, three aspects of personality, namely id, ego, and superego which are the basis of the study, aims to present aspects of inner conflict contained in the novel. The id aspect as the driving force of the ego aspect is interconnected, the driving force of the id is filtered and fulfilled by the ego aspect, and the ego filters and increases the satisfaction sought by the id aspect, so that both balance each other. Furthermore, the novel Rumah Untuk Alie by Lenn Liu presents the superego as a mediator and controller of the problems faced by Alie.